2023
DOI: 10.30736/jt.v15i1.926
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Sentimen Anti LGBT Di Indonesia Melalui Media Sosial Twitter

Abstract: Orang-orang menggunakan media sosial sebagai cara untuk mengekspresikan pikiran, minat, dan pendapat mereka tentang berbagai hal. Ribuan posting muncul di semua jejaring sosial setiap hari. Setiap orang bebas mengungkapkan pendapatnya melalui jejaring sosial. Pendapat ini memiliki perasaan positif, negatif dan netral pada subjek. Studi kasus yang dilakukan peneliti adalah kampanye melawan LGBT di Indonesia. Kasus ini diambil karena kampanye melawan LGBT ramai diperbincangkan oleh masyarakat Indonesia di media … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
0
0
3
Order By: Relevance
“…In previous studies, research was conducted regarding the anti-LGBT campaign by (Ardras & Voutama, 2023) on Twitter social media using the Naive Bayes method on rapid miners with a data ratio of 60:40. The results showed that 55% of the data classified had neutral sentiment and 45% supported anti-LGBT, while negative perceptions arise due to public disappointment with anti-LGBT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, research was conducted regarding the anti-LGBT campaign by (Ardras & Voutama, 2023) on Twitter social media using the Naive Bayes method on rapid miners with a data ratio of 60:40. The results showed that 55% of the data classified had neutral sentiment and 45% supported anti-LGBT, while negative perceptions arise due to public disappointment with anti-LGBT.…”
Section: Discussionmentioning
confidence: 99%
“…This proves that logistic regression is more suitable among the five methods used in the study. Recent research was also conducted by (Ardras & Voutama, 2023) regarding anti-LGBT campaigns on Twitter social media using the Naïve Bayes method on rapid miners with a data ratio of 60:40, and the results show that 55% of the data classified as neutral sentiment and 45% are in support of anti-LGBT, while negative perceptions arise due to public disappointment with anti-LGBT.…”
Section: Introductionmentioning
confidence: 99%
“…Twitter adalah salah satu media sosial paling populer di kalangan pengguna internet [10]. Hal tersebut disebabkan oleh penggunaannya yang sederhana dan mudah, serta pemakai dapat mengungkapkan pendapat atau opini mereka dengan bebas [9].…”
Section: Pendahuluanunclassified
“…Analisis sentimen merupakan salah satu kasus text mining yang merujuk pada proses penggunaan teknik-teknik komputasional untuk mengidentifikasi, mengekstraksi, dan memahami sentimen atau opini yang terkandung dalam teks atau data unstruktural, dengan tujuan mendapatkan wawasan yang berharga dari data tersebut [6]. Analisis sentimen, sebagai bagian dari data mining dan text mining, melibatkan penggunaan berbagai algoritma dan metode komputasional dalam penerapannya [7]. Dalam penelitian ini, algoritma klasifikasi yang digunakan dalam membangun model analisis sentimen adalah Support Vector Machine (SVM) dan K-Nearest Neighbor (KNN).…”
Section: Pendahuluanunclassified